Monitoring and Understanding Urban Transformation: A Mixed Method Approach - Bannan, Thomas J.; Evans, James; Benton, Jack S.; Edwards, Pete; Diez, Sebastian; Marsden, Nicholas; Flynn, Michael; Coe, Hugh; Burke, Clare; Murabito, Ettore; Anderson, Jamie; Cruickshank, Sheena M.; et al. (Frontiers in Sustainable Cities, 2022)
Cities must address many challenges including air quality, climate change and the health and wellbeing of communities. Public authorities and developers increasingly look to improve these through the implementation of interventions and innovations, such as low traffic neighbourhoods, deep housing retrofits and green infrastructure. Monitoring the impacts of interventions is essential to determine the success of such projects and to build evidence for broader urban transformation. In this paper we present a mixed-method cross-disciplinary approach that brings together cutting edge atmospheric and data science, measurements of activity in public spaces and novel methods to assess wellbeing-promoting behaviours. The Manchester Urban Observatory focuses on living areas that have a high density of inter-related systems, which require observation, understanding and intervention at multiple levels. This must be completed in line with urban planning goals as well as a clear and succinct data solution that allows robust scientific conclusions to be made and viewed in real time. Delivery of such a monitoring strategy is not trivial and is time, resource and expertise heavy. This paper discusses the methods employed by the Manchester Urban Observatory to monitor the effectiveness off interventions implemented within cities and effective communication strategies with local communities.